IGF-1 downregulates matrix metalloproteinase 8 to promote plaque stability: Evidence from myeloid cell-specific MMP8 in atherosclerosis - Patricia Snarski; Sergiy Sukhanov; Tadashi Yoshida; Svitlana Danchuk; Andrew Gross; Fareed Sindi; Vikara Rivera-Lopez; Patrice Delafontaine; Yusuke Higashi (PLoS ONE, 2025)
Background & aims Macrophages (MF) play an important role in atherosclerosis, a chronic inflammatory disease. Matrix metalloproteinase 8 (MMP8), a collagen degrading enzyme, is expressed by inflammatory cells. Systemic MMP8 deficiency reduces plaque MF and increases collagen suggesting increased plaque stability, however contribution of MF specific MMP8 is unknown. We previously found in Apolipoprotein E-/- mice, Insulin-Like Growth Factor-1 (IGF-1) overexpression in MF reduced MMP8, decreased atherosclerotic plaque MF, and upregulated features of stable atherosclerotic plaque. Thus, we hypothesized that MF specific MMP8 deficiency would reduce plaque burden and promote stability. Methods We used human THP-1 and murine MMP8 deficient MF for in vitro investigation of IGF-1 effect. We generated mice with MF MMP8-deficiency (mM8-:M8 + mice) or MF MMP8-rescue (mM8+ :M8-) by bone marrow transplantation after irradiation; IGF-1 was administered to these and control mice. Results We found IGF-1 reduced MMP8 and suppressed collagenase activity in cultured MF. In Apolipoprotein E-/- mice, MF specific IGF-1 overexpression decreased plaque MMP8 levels and pro-inflammatory cytokines. MMP8 deficient MF had decreased levels of M1 markers and increased expression of M2 markers. We found no difference in atherosclerotic burden between groups, moreover, the ability of IGF-1 to increase collagen production depends on the ability of macrophages to express MMP8. This in vivo effect was only found in females. Conclusions IGF-1 downregulated plaque MMP8 levels in control mice, however this effect was markedly blunted in mM8-:M8 + mice showing that macrophages are the main target of IGF-1 downregulation of plaque MMP8. Overall, our results suggest that macrophage MMP8 may be a potential target to treat unstable atherosclerotic plaques.